A comprehensive review of flow chemistry techniques tailored to the flavours and fragrances industries - Gambacorta, Guido; Sharley, James S.; Baxendale, Ian R. (Beilstein Journal of Organic Chemistry, 2021)
Due to their intrinsic physical properties, which includes being able to perform as volatile liquids at room and biological temperatures, fragrance ingredients/intermediates make ideal candidates for continuous-flow manufacturing. This review highlights the potential crossover between a multibillion dollar industry and the flourishing sub-field of flow chemistry evolving within the discipline of organic synthesis. This is illustrated through selected examples of industrially important transformations specific to the fragrances and flavours industry and by highlighting the advantages of conducting these transformations by using a flow approach. This review is designed to be a compendium of techniques and apparatus already published in the chemical and engineering literature which would constitute a known solution or inspiration for commonly encountered procedures in the manufacture of fragrance and flavour chemicals.
Keywords: flavours and fragrances; flow chemistry; process chemistry; synthesis